2021
DOI: 10.3389/fimmu.2021.752380
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Is a Multi-Organ Aggressor: Epigenetic and Clinical Marks

Abstract: The progression of coronavirus disease 2019 (COVID-19), resulting from a severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, may be influenced by both genetic and environmental factors. Several viruses hijack the host genome machinery for their own advantage and survival, and similar phenomena might occur upon SARS-CoV-2 infection. Severe cases of COVID-19 may be driven by metabolic and epigenetic driven mechanisms, including DNA methylation and histone/chromatin alterations. These epigenet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 300 publications
(399 reference statements)
0
23
0
Order By: Relevance
“…Furthermore, a significant increase in ALT and AST levels was characteristic for patients with uninfected liver tissue (No. 1,7,8,11,16) and patients with high SARS-CoV-2 VL in the liver (No. 4, 12, 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a significant increase in ALT and AST levels was characteristic for patients with uninfected liver tissue (No. 1,7,8,11,16) and patients with high SARS-CoV-2 VL in the liver (No. 4, 12, 1).…”
Section: Resultsmentioning
confidence: 99%
“…COVID-19, as a multisystemic pathology, has led to more than 5 million deaths worldwide to date [1]. A severe course and fatal outcomes of the disease are commonly associated with the severe acute respiratory syndrome (ARDS) and multi-organ failure [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Publications focusing on the role of host genetic factors in determining susceptibility to SARS-CoV-2 infection and COVID-19 severity have included epigenetic, mitochondrial, candidate gene, and genome-wide association studies (GWAS) as well as the use of whole exome sequencing and whole genome sequencing (WGS) ( Ellinghaus et al, 2020 ; Zhang et al, 2020 ; Chlamydas et al, 2021 ; Kgatle et al, 2021 ; Scozzi et al, 2021 ; Sen et al, 2021 ; Velavan et al, 2021 ; Wu et al, 2021 ). One of the earlier human genetic studies included a GWAS of SARS-CoV-2 respiratory failure, which identified associations with the ABO blood locus and a chromosome 3 gene cluster ( SLC6A20 , LZTFL1 , CCR9 , FYCO1 , CXCR6 and XCR1 ) in Italian and Spanish populations ( Ellinghaus et al, 2020 ).…”
Section: Human Genetic Studies Of Sars-cov-2 Infection and Covid-19 S...mentioning
confidence: 99%
“…It also indicates towards a prenatal link between maternal SARS-CoV-2 infection and altered DNA methylation. Kgatle et al [ 29 ] and Papakonstantinou et al [ 30 ] have also discussed epigenome in the context of COVID-19 and heart.…”
Section: Altered Epigenomic Signature Of Dna Methylation In Heart Imp...mentioning
confidence: 99%
“…Since epigenome-based therapies are an upcoming and promising field, it is necessary to explore their potential in our battle against an unfamiliar enemy when there is a lack of current preventative strategy. In this direction, few studies have investigated the epigenome upon SARS-CoV-2 infection to find several alterations in DNA methylation which is a major epigenetic signature, and some of these studies investigated the heart [ 26 , 27 , 28 , 29 , 30 ]. Consequently, altered DNA methylation has led to changes in the expression of several genes.…”
Section: Introductionmentioning
confidence: 99%